DECOLONIZING MI'KMAW EDUCATION THROUGH CULTURAL PRACTICAL KNOWLEDGE - Orr, Jeff; Paul, San Salom / John Jerome; Paul, Kelusilew / Sharon (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2002)
ABSTRACT. This article shares the stories of three Mi'kmaw teachers who are bringing their Aboriginal cultural practical knowledge into the school landscape through pedagogy and relationality, as they work towards the decolonization of their education system. Our notion of cultural practical knowledge relates to Connelly & Clandinin's personal practical knowledge. It is connected to the Mi'kmaw stories these teachers and their students construct and re-construct together as they work towards understanding and supporting the needs of students through applying teachers' own cultural practical knowledge. DÉCOLONISATION DE L'ÉDUCATION MI'KMAQ PAR LA CONNAISSANCE PRATIQUE CUlTURELLE RÉSUMÉ. Cet article relate l'histoire de trois professeurs mi'kmaw qui mettent à contribution leurs connaissances pratiques culturelles autochtones dans le paysage scolaire par la pédagogie et la relationalité, tandis qu'ils s'évertuent à décoloniser leur système d'éducation. Notre notion de la connaissance pratique culturelle se rapporte à la connaissance pratique personnelle de Connelly et Clandinin. Elle est liée aux récits mi'kmaw que ces enseignants et leurs élèves construisent et reconstruisent ensemble afin de comprendre et de répondre aux besoins des élèves grâce à l'application des connaissances pratiques culturelles des enseignants.